English Teachers’ Perceptions of Digital Literacy in Teaching - Imam Santosa; Stephanie Fahra Caroline; Ifan Iskandar; Vjollca Jonuzi (CV Media Inti Teknologi, 2025)
Background of the Study: Digital literacy has become a crucial aspect of modern education. English teachers are expected to not only use digital tools but also understand their pedagogical and ethical implications. Aims and Scope of the Paper: This study explores the perceptions of junior and senior high school English teachers regarding digital literacy in teaching, including their experiences, challenges, and readiness in integrating digital tools. Methods: Using a descriptive qualitative approach, data were collected through semi-structured interviews with 17 English teachers who met the inclusion criteria. Thematic analysis was employed to identify patterns and themes. Results: The analysis revealed four main themes: access, evaluation, use, and reflection. Teachers showed enthusiasm in using digital tools, but practices remained within familiar boundaries. Formal training in evaluating content was limited, and concerns about ethical and pedagogical responsibilities emerged. Conclusion: Effective integration of digital literacy requires not only access to tools and infrastructure but also continuous professional development that promotes confidence, critical awareness, and reflective teaching practices.